2011
DOI: 10.1002/elps.201100086
|View full text |Cite
|
Sign up to set email alerts
|

Development of a double‐layer microfluidic chip with flow medium for chemotherapy resistance analysis of lung cancer

Abstract: Integration and miniaturization are main advantages of microchip-based systems. Vertical integration of the multiple operations within a multiple-layer chip is expected to satisfy the urgent demand for high-throughput and large-scale applications. This study aimed at establishing a double-layer chip to integrate the operations including the cell culture, the identification of the protein and the detection of the cell viability onto a platform systematically and supplied with flow fresh medium continuously via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The standard CTCs purification protocol would leave few WBCs among them and thus they remains to be identified. To accomplish this, rat-tail collagen (0.012 mg/mL, Solarbio, China) was used to coat the chamber, because CTCs, based on antigen-antibody immune affinity, adhered better on the coated surface 50 .…”
Section: Methodsmentioning
confidence: 99%
“…The standard CTCs purification protocol would leave few WBCs among them and thus they remains to be identified. To accomplish this, rat-tail collagen (0.012 mg/mL, Solarbio, China) was used to coat the chamber, because CTCs, based on antigen-antibody immune affinity, adhered better on the coated surface 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Microstructured membranes deployed inside microfluidic channels offer unique advantages in terms of entrapment of cells and analysis of cellular contents. [37][38][39][40][41] The goal of this study was to incorporate aptasensors for cell analysis reported by us previously 25,29 into reconfigurable microfluidic devices. As shown in the schematic of Fig.…”
Section: Microfluidic Device Actuationmentioning
confidence: 99%